Development of RS1-specific ACMG/AMP variant classification criteria with pilot variant curation - Sarah Hull; M. Mero; W. Hankey; K. Lee; L. S. Sullivan; R. Ayyagari; M. D. Benson; L. Haer-Wigman; R. B. Hufnagel; H. M. J. Hussain; K. Kämpjärvi; P. A. Sieving; et al. (Human Genetics, 2026)
Gene-based therapies are being developed for retinal diseases, including RS1- related X-linked retinoschisis. Therefore it is essential to determine which variants are pathogenic and which are benign when enrolling patients. The Clinical Genome Resource (ClinGen) X-Linked Inherited Retinal Diseases (XLRD) Variant Curation Expert Panel (VCEP) brings together clinician scientists, molecular biologists, and geneticists to apply their expertise and review the clinical, genetic, population, and functional evidence for variants. American College of Medical Genetics (ACMG) guidelines have been modified for RS1 to develop a highly systematic and conservative framework for evaluating variants. The curation process involves applying 28 different codes, each with 4 strength levels (very strong, strong, moderate, supporting) across different domains of phenotype, population data, computational assessment, functional impact, and segregation. With RS1- specific rules, a total of 54 pilot variants were tested. These included 47 variants in ClinVar. Of these 21 variants were re-classified: 2 likely pathogenic variants and one likely benign were changed to variants of uncertain significance and 4 previously unclassified variants were changed to pathogenic, likely pathogenic and likely benign. Other changes resolved conflicts or multiple classifications.

Impact of socioeconomic status on cancer incidence and stage at diagnosis: selected findings from the surveillance, epidemiology, and end results: National Longitudinal Mortality Study - Limin X. Clegg; Marsha E. Reichman; Barry A. Miller; Benjamin F. Hankey; Gopal K. Singh; Yi Dan Lin; Marc T. Goodman; Charles F. Lynch; Stephen M. Schwartz; Vivien W. Chen; Leslie Bernstein; Scarlett L. Gomez; et al. (Cancer Causes & Control, 2009)

Quality of race, Hispanic ethnicity, and immigrant status in population-based cancer registry data: implications for health disparity studies - Limin X. Clegg; Marsha E. Reichman; Benjamin F. Hankey; Barry A. Miller; Yi D. Lin; Norman J. Johnson; Stephen M. Schwartz; Leslie Bernstein; Vivien W. Chen; Marc T. Goodman; Scarlett L. Gomez; John J. Graff; et al. (Cancer Causes & Control, 2007)